Study of Sexual Dimorphism in Metatarsal Bones: Geometric and Inertial Analysis of the Three-Dimensional Reconstructed Models - Liu, Yaming; Antonijević, Djorde; Li, Ruining; Fan, Yuxuan; Dukić, Ksenija; Mićić, Milutin; Yu, Genyu; Li, Zhiyu; Djurić, Marija; Fan, Yifang (Frontiers in Endocrinology, 2021)
The aim of the present paper is to determine the sex of the individual using three-dimensional geometric and inertial analyses of metatarsal bones. Metatarsals of 60 adult Chinese subjects of both sexes were scanned using Aquilion One-320 Slice CT Scanner. The three-dimensional models of the metatarsals were reconstructed and thereafter a novel software using the center of mass set as the origin and the three principal axes of inertia was employed for model alignment. Eight geometric and inertial variables were assessed: the bone length, bone width, bone height, surface-area-to-volume ratio, bone density and principal moments of inertia around x, y and z axis. Furthermore, the discriminant functions were established using stepwise discriminant function analysis. A cross-validation procedure was performed to evaluate discriminant accuracy of functions. The results indicated that inertial variables exhibit significant sexual dimorphism, especially principal moments of inertia around z axis. The highest dimorphic values were found in surface-area-to-volume ratio, principal moments of inertia around z axis and bone height. The accuracy rate of the discriminant functions for sex determination ranged from 88.3% to 98.3% (88.3% - 98.3% cross-validated). The highest accuracy of function was established based on the 3rd metatarsal bone. This study showed for the first time that the principal moment of inertia of the human bone may be successfully implemented for sex estimation. In conclusion, the sex of the individual can be accurately estimated using a combination of geometric and inertial variables of the metatarsal bones. The accuracy should be further confirmed in a larger sample size and be tested or independently developed for distinct population/age groups before the functions are widely applied in unidentified skeletons in forensic and bioarchaeological contexts.